School punishment, deterrence, and race: a partial test of defiance theory - Pesta, Racheal (Crime & delinquency, 2022)
Rather than serving as a deterrent, exclusionary discipline tends to lead to a host of short and long-term negative outcomes. The mechanisms which propel students from exclusionary discipline toward these negative outcomes is understudied. The negative impact of school sanctions is particularly salient among students of color; yet the reasons for this are unclear. Informed by Sherman’s defiance theory, this study utilizes data from the National Longitudinal Study of Adolescent and Adult Health (Add Health) to identify these mechanisms among a sample of white and black students. Results suggest that defiance theory provides a theoretically relevant framework for understanding the impact of school sanctions on future outcomes as well as how the effects vary across race.